COMPARATIVE INSIGHTS INTO LABOUR PRODUCTIVITY TRENDS IN THE EUROPEAN UNION'S AGRI-FOOD SECTOR - Dragoș SMEDESCU; Valentina TUDOR; Marius Mihai MICU; Liviu MĂRCUȚĂ; Alina MĂRCUȚĂ; Cosmina SMEDESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The agri-food sector stands as a fundamental pillar of the European Union's economic framework, essential for sustaining the region’s population and playing a significant role in the overall economic health and stability of the EU. This study offers a comprehensive analysis of labor productivity trends in the EU's agri-food sector over the past decade, focusing on a comparative assessment between Romania and top-performing EU economies. Using data from Eurostat and national databases, we explore the dynamics of labor productivity, considering factors such as turnover, number of enterprises, and employment levels in the agri-food industry. The research reveals significant disparities in productivity growth, with countries like the Netherlands, Denmark, and Belgium showing high productivity levels, while Romania, despite a notable improvement, remains below the EU average. The study underscores the importance of strategic investments and policy interventions in boosting productivity and competitiveness in the agri-food sector across Europe.